Better together : creating community in an uncertain world - Tate, Nikki, 1962- (Orca footprints., 2018)
Examines different types of families, communities, and cultures around the world, and expresses the importance of community for providing love, acceptance, safety, and security. Highlights different types of groups from the smallest units of parents to global organizations. Also discusses the need for people to get involved in order to make the world a better place. Includes fact boxes, color photographs, a glossary, and further resources.